2015
DOI: 10.7589/2014-10-253
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure Risk from Trash Ingestion by the Endangered California Condor (Gymnogyps californianus)

Abstract: ABSTRACT:Lead poisoning from ingestion of spent lead ammunition is one of the greatest threats to the recovery of California Condors (Gymnogyps californianus) in the wild. Trash ingestion by condors is well documented, yet the extent that trash presents a lead exposure risk is unknown. We evaluated 1,413 trash items collected from condor nest areas and nestlings in the Transverse Range of Ventura County, California, US, from 2002 to 2008, for their potential as a lead exposure risk to condors. We visually iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, they only avoided those > 8.8 mm, which is considerably larger than most gunshot or bullet fragments. Analyses of ‘trash’ items from the nest area of California condors ( Gymnogyps californianus ) (Finkelstein et al 2015) and a literature review (Golden et al 2016) confirmed the view that, while different sources of lead are available in the landscape, most lead poisoning of scavenging birds appears to result from lead-based ammunition ingested in their food. Low tissue lead levels (liver lead < 2.1 ppm dw; N = 11) have been reported in the lesser-spotted eagle ( Clanga pomarina brehm ), a species that breeds in Europe but migrates to Africa, thus avoiding the European hunting season (Kitowski et al 2017c).…”
Section: Pathways Of Exposurementioning
confidence: 98%
“…However, they only avoided those > 8.8 mm, which is considerably larger than most gunshot or bullet fragments. Analyses of ‘trash’ items from the nest area of California condors ( Gymnogyps californianus ) (Finkelstein et al 2015) and a literature review (Golden et al 2016) confirmed the view that, while different sources of lead are available in the landscape, most lead poisoning of scavenging birds appears to result from lead-based ammunition ingested in their food. Low tissue lead levels (liver lead < 2.1 ppm dw; N = 11) have been reported in the lesser-spotted eagle ( Clanga pomarina brehm ), a species that breeds in Europe but migrates to Africa, thus avoiding the European hunting season (Kitowski et al 2017c).…”
Section: Pathways Of Exposurementioning
confidence: 98%
“…Laying to fledging typically requires ∼8 months and adults provide parental care after fledging, especially for the first 6 months, resulting in a general pattern of biennial breeding (Finkelstein et al 2020). California Condors have faced two well-documented anthropogenic threats to reproduction: reduced hatching success due to egg-shell thinning, attributed to DDE exposure from feeding on marine mammals (Burnett et al, 2013, Kurle et al, 2016) and reduced fledgling success from chicks ingesting trash (e.g., bottle caps, washers, bolts, fabric, plastic; Mee et al 2007b, Finkelstein et al 2015). Seeking to maximize reproductive success, managers have closely monitored nests and instituted a variety of interventions, including swapping captive-laid eggs for wild eggs, removing trash in the vicinity of nests, and evacuating chicks with impacted crops or other life-threatening conditions for medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of chemical contaminants on apex predators, particularly birds, have been well studied over the last 50 years. This is partly because exposure to a diverse range of contaminants, including toxic heavy metals (such as lead), insecticides, biocides and pharmaceuticals, has resulted in lethal poisoning and/or impaired reproduction that, in some cases, has directly led to global population declines [1][2][3][4][5][6]. Detection of populationlevel effect is arguably easier in birds than for many other animals.…”
Section: Introductionmentioning
confidence: 99%